Expanding the Physiological Role of Aryl-Alcohol Flavooxidases as Quinone Reductases - Ferreira, Patricia; Carro, Juan; Balcells, Beatriz; Martínez, Angel T.; Serrano, Ana (Applied and environmental microbiology, 2023)
In this work, quinone reductase activity is analyzed in three AAO flavooxidases, whose preferred oxidizing-substrate is O 2 . The results presented, including reactions in the presence of both oxidizing substrates—benzoquinone and molecular oxygen—suggest that such aryl-alcohol dehydrogenase activity, although less important than its oxidase activity in terms of maximal turnover, may have a physiological role during fungal decay of lignocellulose by the reduction of quinones (and phenoxy radicals) from lignin degradation, preventing repolymerization. Aryl-alcohol oxidases (AAOs) are members of the glucose-methanol-choline oxidase/dehydrogenase (GMC) superfamily. These extracellular flavoproteins have been described as auxiliary enzymes in the degradation of lignin by several white-rot basidiomycetes. In this context, they oxidize fungal secondary metabolites and lignin-derived compounds using O 2 as an electron acceptor, and supply H 2 O 2 to ligninolytic peroxidases. Their substrate specificity, including mechanistic aspects of the oxidation reaction, has been characterized in Pleurotus eryngii AAO, taken as a model enzyme of this GMC superfamily. AAOs show broad reducing-substrate specificity in agreement with their role in lignin degradation, being able to oxidize both nonphenolic and phenolic aryl alcohols (and hydrated aldehydes). In the present work, the AAOs from Pleurotus ostreatus and Bjerkandera adusta were heterologously expressed in Escherichia coli , and their physicochemical properties and oxidizing abilities were compared with those of the well-known recombinant AAO from P. eryngii. In addition, electron acceptors different from O 2 , such as p -benzoquinone and the artificial redox dye 2,6-Dichlorophenolindophenol, were also studied. Differences in reducing-substrate specificity were found between the AAO enzymes from B. adusta and the two Pleurotus species. Moreover, the three AAOs oxidized aryl alcohols concomitantly with the reduction of p -benzoquinone, with similar or even higher efficiencies than when using their preferred oxidizing-substrate, O 2 . IMPORTANCE In this work, quinone reductase activity is analyzed in three AAO flavooxidases, whose preferred oxidizing-substrate is O 2 . The results presented, including reactions in the presence of both oxidizing substrates—benzoquinone and molecular oxygen—suggest that such aryl-alcohol dehydrogenase activity, although less important than its oxidase activity in terms of maximal turnover, may have a physiological role during fungal decay of lignocellulose by the reduction of quinones (and phenoxy radicals) from lignin degradation, preventing repolymerization. Moreover, the resulting hydroquinones would participate in redox-cycling reactions for the production of hydroxyl free radical involved in the oxidative attack of the plant cell-wall. Hydroquinones can also act as mediators for laccases and peroxidases in lignin degradation in the form of semiquinone radicals, as well as activators of lytic polysaccharide monooxygenases in the attack of crystalline cellulose. Moreover, reduction of these, and other phenoxy radicals produced by laccases and peroxidases, promotes lignin degradation by limiting repolymerization reactions. These findings expand the role of AAO in lignin biodegradation.